Characterization and Processing of Complex Materials - Otsuki, Akira (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint provides a forum for scientists and engineers to share and discuss their pioneering/original findings or insightful reviews on the "Characterization and Processing of Complex Materials". Reports on successfully coupling complex industrial materials/waste/natural ores with non-destructive characterization method(s) and the unique processing developments were particularly encouraged. On the other hand, any kind of contribution under the broad framework of the understanding and production of complex materials was also highly regarded. This reprint gathers papers on the characterization and processing of complex materials with the following keywords: non-destructive characterization; analytical chemistry and instrumentation; waste management and recycling; selective material recovery/processing; sustainability and circular economy. This includes the waste management and recycling of complex materials (e.g., food and electronic waste) through the development of a new characterization method and/or process intensification. For example, the proper characterization of complex/heterogeneous materials is still an extremely challenging task, since the majority of characterization methods analyze either the average characteristics of the whole material or a narrow area of specific interest. On the other hand, the efficient processing/recycling of complex materials/waste should be strongly supported by their characterization from the viewpoint of economic and environmental concerns.